1999
DOI: 10.1093/intimm/11.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of acute inflammatory lung injury induced by abdominal sepsis

Abstract: Sequestration of neutrophils and release of histotoxic mediators are considered important for the development of pathologic alterations of the lung defined as adult respiratory distress syndrome. Mechanisms of inflammatory lung injury caused by abdominal sepsis were investigated using the colon ascendens stent peritonitis (CASP) model that closely mimics the human disease. In the CASP model, a continuous leakage of intraluminal bacteria into the peritoneal cavity is induced by implantation of a stent in the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 66 publications
5
57
0
2
Order By: Relevance
“…It has long been known that in systemic inflammatory states, peripheral PMN lose their responsiveness to CXC chemokines (54,55). Our work poses the question of whether these cells might gain responsiveness to CC chemokines, providing a possible mechanism for the PMN-mediated tissue damage associated with a variety of inflammatory conditions (55,56). Such scenarios of local and systemic PMN activation and responsiveness to CC chemokines lead to new and interesting questions on PMN participation in cytokine networks and in the pathogenesis of inflammatory lesions.…”
Section: Discussionmentioning
confidence: 83%
“…It has long been known that in systemic inflammatory states, peripheral PMN lose their responsiveness to CXC chemokines (54,55). Our work poses the question of whether these cells might gain responsiveness to CC chemokines, providing a possible mechanism for the PMN-mediated tissue damage associated with a variety of inflammatory conditions (55,56). Such scenarios of local and systemic PMN activation and responsiveness to CC chemokines lead to new and interesting questions on PMN participation in cytokine networks and in the pathogenesis of inflammatory lesions.…”
Section: Discussionmentioning
confidence: 83%
“…Although locally restricted alterations of IFN-␥ production cannot be excluded, these results suggest that the protective effects of CpG-ODN are not mediated by an enhanced Th1 response. Moreover, the rapid progression of infection and early mortality in the CASP model (34,35) also indicate that host defense is mainly dependent on effector mechanisms of the innate rather than the adaptive immune system. Collectively, our observations provide strong evidence that the immune modulating activities of CpG-ODN are not restricted to the instruction and reprogramming of adaptive immunity but, in addition, may involve the amplification of the innate effector cell response during acute polymicrobial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Production of oxygen metabolites was assessed by a flow cytometric method as described (35). Briefly, heparinized blood from CpG and control ODN-treated mice was collected, and erythrocytes were lysed as described above.…”
Section: Oxidative Burst and Phagocytosismentioning
confidence: 99%
“…Despite significant advances and extensive therapeutic approaches, sepsis remains a major health concern and leading cause of high mortality worldwide (2)(3)(4). Human and animal studies have demonstrated that progressive multiple organ failure is the most common cause of death following sepsis, with the lungs usually representing the first organ to fail (5). Predisposition of the immune response has been shown to be critical in the development of an exaggerated inflammatory reaction and ensuing acute lung injury (ALI) (6).…”
Section: Introductionmentioning
confidence: 99%